GFP-related chromophores: photoisomerization, thermal reversion, and DNA labelling - Faillace, Martín Sebastián (2023)
Due to the pronounced effect of the confined environment on the photochemical properties of 4-hydroxybenzylidene imidazolinone (HBI), a GFP-related chromophore, imidazolidinone and imidazothiazolone analogues have been studied as fluorescent probes. Their photoisomerization and their thermal reversion were studied under 365-nm-irradiation, resulting in observation of an enthalpy-entropy compensation effect. Theoretical studies were carried out to shed light on the thermal reversion mechanism. Moreover, photophysical studies of benzylidene imidazothiazolone in the presence of dsDNA revealed fluorescence enhancement. The prepared compounds could be considered as a valuable tool for the detailed investigation of physicochemical, biochemical, or biological systems.